Reverse reconstruction of two-wheeled vehicle accident based on Facet vehicle model and hybrid human model. Issue 3 (4th May 2022) - Wang, Qian; Lou, Yunfeng; Jin, Xianlong; Kong, Lingshuang; Qin, Chuang; Hou, Xinyi
Abstract: To obtain a rider-vehicle-road coupling system that takes both efficiency and accuracy into account, so that the simulation model of two-wheeled vehicle traffic accident can reduce the calculation time as much as possible on the premise that it can simulate human biomechanical injury and vehicle deformation, this paper proposes a new two-wheeled vehicle accident simulation model. In this method, the vehicle uses the Facet model, and the cyclist uses the hybrid human model. The coupling system of rider-vehicle-road is established and the effectiveness of the system is verified. For the collision accident between the car and two-wheeled vehicle, the simulation model is used to reconstruct in MADYMO. The results show that the motion posture of cyclists and vehicles after the collision is consistent with the accident situation, and the human injury data is consistent with the medicolegal expertise, which verifies the feasibility and effectiveness of this simulation model. This modelling method provides a new idea for the reconstruction of two-wheeled traffic accidents and the general dynamic simulation.